Village Open Data Implementation: Lesson Learned from Alang-alang Vilalge, Madura - Muhammad Yusuf; M Kautsar Sophan; Budi Dwi Satoto; Devie Rosa Anamisa; Nurwahyu Alamsyah (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Alang-alang village is one of the villages in Bangkalan, Madura, near the Suramadu bridge. This village has a vision to be a smart cyber village. However, the application of open data need to be explored, especially in the village area. We just found the implementation of the open data application in Wonosobo and Bantul. Therefore, researching implementing Open data applications at the village level is important. This study aims to capture the open data application 1.0 implementation for the Alang-Alang Village Government. It will explore the richness of the village open data implementation’s success factors, challenges, and uniqueness. This research contributes by providing a lesson learned and a novel model for Village Open Data Implementation based on the case study of the Alang-alang village open data application. Moreover, this research also has some implications for knowledge and practice for other villages’ governments, researchers, practitioners, and village ministries worldwide, such as the implementation model can be adopted for other contexts and villages. In the body of knowledge, it develops a body of e-Government and smart village knowledge and research fields. Based on this case study, there are some success factors for village open data implementation: Vision and commitment of the village leader, regulation, people’s support and participation, infrastructure, and digital literacy.